Al-Hawl Camp-a geographic incubator for a future generation of terrorists threatening Iraqi-Syrian national security - Mustafa Abd Al-Rasool Ahmed (Genius Journals, 2024)
Since the launch of the operations to liberate Nineveh from the terrorist organization ISIS in 2016, which represented the strategic weight of the terrorists, and after their military defeat and loss of their areas of control in Iraq and Syria, displacement movements emerged for those fleeing due to the military operations that their areas witnessed since (2016-2020) to Al-Hawl camp located in the countryside. The eastern governorate of Hasakah, which was reopened by the United Nations High Commissioner for Refugees in 2016, until the Syrian camps, especially Al-Hawl, became a gathering of the families of the dead of the terrorist organization ISIS and detained male and female extremists, to provide an incubating environment for the organization’s ideology, which paves the way for the creation of a new coming generation of terrorists that threatens the security of the region, especially Syria and Iraq at a time when it is difficult to control it by the parties responsible for managing the camp, represented by the Syrian Democratic Forces, and preventing the spread of extremist ideology among its residents
Keywords: Al-Hawl camp; terrorists; national security